Life expectancy and education: Evidence from the cardiovascular revolution - Casper Worm Hansen; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper exploits the unexpected decline of deaths from cardiovascular diseases since the 1970s as a large positive health shock that affected predominantly old-age mortality; i.e., the fourth stage of the epidemiological transition. Using a differences-in-differences estimation strategy, we find that U.S. states with higher levels of cardiovascular-disease mortality prior the 1970s experienced greater increases in adultlife expectancy and higher education enrollment. Our estimates suggest that the cardiovascular revolution caused an increase in life expectancy of 1.5 years and an increase in education enrollment of 9 percentage points, i.e. 52 percent of the observed increase from 1960 to 2000.
Keywords: I15; J24; N30; O10; O40; 330; adult life expectancy; higher education; cardiovascular diseases; differences-in-differences strategy